2020
DOI: 10.1080/14786419.2020.1851220
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic activity of butanolic extract from Sambucus nigra L. flowers in natura and vehiculated in micelles in bladder cancer cells and fibroblasts

Abstract: Bladder cancer has a high incidence and recurrence rate among patients worldwide. This study aimed to evaluate the cytotoxic activity of fractions of Sambucus nigra L. flower extracts on bladder carcinoma cells (T24 cells) and human fibroblast cells (MRC -5). The butanolic fraction (F-BuOH) was characterized by UPLC-DAD-MS/MS and nine flavonoids were identified. Rutin was the major compound. The cytotoxic activity of this fraction was observed in the T24 cells but not in MRC-5 cells, indicating selectivity. F-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…They could decrease the viability of the tested cell lines via the synergistic effects of (poly)­phenolic compounds, and the molecular docking study indicated that chlorogenic acid and rutin had the ability to interact with key amino acids in the Bcl-2 binding site . In T24 bladder carcinoma cells and MRC-5 human normal fibroblast cells, the cytotoxic activity of elderberry flower extracts could only be observable in T24 cells but not in MRC-5 cells, suggesting that the elderberry flower extracts are toxic to cancer cells but safe to normal cells, and flavonoids identified in the extract were possibly responsible for the cytotoxic activity . Moreover, micellar solutions of pluronic F127 could enhance the cytotoxic activity .…”
Section: Health Functions Of Elderberrymentioning
confidence: 99%
See 2 more Smart Citations
“…They could decrease the viability of the tested cell lines via the synergistic effects of (poly)­phenolic compounds, and the molecular docking study indicated that chlorogenic acid and rutin had the ability to interact with key amino acids in the Bcl-2 binding site . In T24 bladder carcinoma cells and MRC-5 human normal fibroblast cells, the cytotoxic activity of elderberry flower extracts could only be observable in T24 cells but not in MRC-5 cells, suggesting that the elderberry flower extracts are toxic to cancer cells but safe to normal cells, and flavonoids identified in the extract were possibly responsible for the cytotoxic activity . Moreover, micellar solutions of pluronic F127 could enhance the cytotoxic activity .…”
Section: Health Functions Of Elderberrymentioning
confidence: 99%
“…58 In T24 bladder carcinoma cells and MRC-5 human normal fibroblast cells, the cytotoxic activity of elderberry flower extracts could only be observable in T24 cells but not in MRC-5 cells, suggesting that the elderberry flower extracts are toxic to cancer cells but safe to normal cells, and flavonoids identified in the extract were possibly responsible for the cytotoxic activity. 59 Moreover, micellar solutions of pluronic F127 could enhance the cytotoxic activity. 59 In a dysplastic oral keratinocyte model, the effects of elderberry fruit extract and silver nanoparticles capped with (poly)phenolics from the extract (AgSN) on cell viability and apoptosis were evaluated, and the results showed that the extract induced cell death in the dysplastic oral keratinocyte model by increasing the DNA lesions and the autophagic response, while AgSN induced dysplastic oral keratinocyte death through necrosis, DNA lesions, and autophagy.…”
Section: ■ Health Functions Of Elderberrymentioning
confidence: 99%
See 1 more Smart Citation
“…Elderberry flowers can be used both for prevention and therapy of a wide array of diseases due to immunomodulatory [42,43], antiinflammatory [44][45][46], antioxidant [28,[47][48][49][50], antimicrobial [12,51,52] and antiviral [41,53,54] activities. In vitro experiments demonstrated the ability of elderberry extract or its constituents to suppress proliferation and viability of various cancer cell lines [25,33,[55][56][57][58] and to prevent angiogenesis in tumor [55,59]. On the other hand, in some cases (estrogenic breast cancer cells and osteosarcoma cells), the biomolecule rutin found in the black elderberry did not affect cancer cell viability [60].…”
Section: Physiological and Therapeutic Actions Of Elderberry And Its ...mentioning
confidence: 99%
“…Protective effect against breast cancer by reduction of cell proliferation; inhibition of estrogen secretion, downregulation of ERα and upregulation of PR [57] Butanolic elderflower extract Bladder carcinoma cells T24 and human fibroblast cells MRC-5 Selective cytotoxic activity in cancer cells [58] Sambucus Wistar white male rats, streptozotocin (STZ)-induced hyperglycemic rats Reduction in the body fat in diabetic rats; decrease in the lipid peroxidation level in serum [70] Methanol elderflower extract Primary porcine myotube cultures Modulation of glucose; increase in glucose uptake [71] Antiosteoporosis activity Methanol polyphenolic elderberry fruit extract…”
Section: Anticancer Activitymentioning
confidence: 99%